Correlation of orthostatic hypotension with extracranial carotid and intracranial cerebral arteries atherosclerosis in patients with acute ischemic stroke under cerebral angiography. Issue 5 (18th March 2021) - Tang, Xianbi; Wu, Bin; Liu, Li; Yi, Ziwei; Shao, Xi; Jing, Kaiquan; Fan, Jiangli; Pan, Chuzheng
Abstract : Objective: The clinical management of patients with acute ischemic stroke (AIS) is complicated by orthostatic hypotension, which might have close relationship with the atherosclerosis of cerebral arteries. The primary objectives were to evaluate the relationship of orthostatic hypotension with extracranial carotid arteries atherosclerosis (ECAS) and intracranial atherosclerosis (ICAS) in AIS patients. Methods: This study was a prospective cohort analysis of consecutive AIS patients under cerebrovascular angiography. A total of 289 patients were included. orthostatic hypotension was defined as a systolic BP decline ≥20 mmHg or a diastolic BP decline ≥10 mmHg within 3 min of standing. Univariate and multivariate analysis were performed to investigate the association of the clinical variables with orthostatic hypotension. Results: Orthostatic hypotension was identified in 80 (27.7%) of all patients. ECAS (≥70%) and ICAS (≥50%) was found in 39 (13.5%) and 71 (24.6%) respectively. In multivariate analysis, only diabetes mellitus (odds ratio = 2.00, 95% confidence interval, 1.12–3.58, P = 0.019) and ECAS (odds ratio = 1.97, 95% confidence interval, 1.54–2.51, P < 0.001) were independent risk factors for orthostatic hypotension. Conclusions: Orthostatic hypotension is a relatively common finding among patients with AIS. AIS patients should be screened for orthostatic hypotension, especially combined with severe ECAS and diabetes mellitus.